Self-assembly of a Ni(I)-photocatalyst for plain water splitting without sacrificial agents - Qin, Shanshan; Badura, Zdenek; Denisov, Nikita; Tomanec, Ondrej; Mohajernia, Shiva; Liu, Ning; Kment, Stepan; Zoppellaro, Giorgio; Schmuki, Patrik (Electrochemistry Communications, 2021)
The present work describes a self-assembling photocatalytic system that is observed when illuminating grey titania nanoparticles in suspension with a plain aqueous Ni2+ solution. Such a suspension (in contrast to white titania), under UV illumination, increasingly produces H2 from neutral water. We show that the origin of this self-activation is not the light-induced deposition of Ni0 or another Ni-catalyst compound on the titania surface. Rather, in-situ electron paramagnetic resonance (EPR) clearly indicates that the activation is due to a light-induced formation of a suitable defect structure (Ti3+-OV) on grey titania, combined with the formation of an intermediate monovalent nickel (Ni(I)) electron transfer relay. Remarkably, the resulting Ni+/TiO2/Ti3+ photocatalyst operates in absence of any noble metal or sacrificial agent.
CRIS-Team Scopus Importer:2021-01-22
Keywords: Hydrogen evolution; Hydrogenated anatase titania; Ni(I)-photocatalyst; Plain water splitting; Self-assembly